Screen printed novel ZnO/MWCNTs nanocomposite thick films. Issue 5 (1st March 2021) - Zargar, Rayees Ahmad; Arora, Manju; Alshahrani, T.; Shkir, Mohd
Abstract: Zinc oxide and multiwall carbon nanotubes (ZnO/MWCNT) nanocomposites thick films were prepared via sol-gel screen printing procedure and followed by sintering at 550 °C. Thus, the prepared films were characterized using X-ray diffraction (XRD), scanning electron microscope (SEM), Ultraviolet–visible (UV–vis), Photoluminescence (PL), Fourier transform infrared (FTIR), Raman spectroscopy and Two-probe method. XRD analysis revealed (101) orientation for both ZnO and ZnO/MWCNT thick films with wurtzite structure. SEM studies confirmed the porous nature of ZnO film while ZnO/MWCNT films showed ZnO particles trapped in the porous MWCNT network and free from cracks. Reflectance spectroscopy showed direct transition with decreasing band gap whereas refractive index and absorption index showed appreciable variation within the band gap regime related to the change in crystallite size. FTIR profile approved the Zn–O stretching and presence of carboxylic CDC group. The PL spectrum of ZnO and ZnO/MWCNT thick films shows red shift and exhibits UV, blue and green emissions confirmed from CIE diagram. Raman spectrum shows that Raman phonons are shifted and dominated due to doping of MWCNT in ZnO matrix. Electrical properties were investigated using 2-probe method and showed a reduction in resistance on MWCNT incorporation. The novelty of current-work is the fabrication of ZnO/MWCNT through a low-cost screen printing process for the first time and the results exhibits that the bandgap of the deposited film is decreased, which in turn, play a significant role in enhancement of conductivity and colour emission for fabrication of low cost optoelectronics devices (LEDs) as compared with the pure ZnO film.